Evaluation of serum thyroid hormones in female patients with melasma - Zhwan Amjad Kamal; Ali Mozan Dhahir Elethawi (Advanced Medical Journal)
Background & Objectives: Melasma is an acquired hyperpigmented patches dispersed symmetrically on body parts that are exposed to the sun, mostly on the faces of female patients. The precise etiology is obscure, but it has numerous hazards such as; ultraviolet exposure, genetic factors, and hormonal imbalances like thyroid hormone abnormalities. In this study, we aimed to evaluate serum thyroid hormone levels in melasma patients.